Peran Bimbingan Penyuluhan Oleh Satuan Binmas Dalam Mencegah Tindak Pidana Penipuan Di Wilayah Hukum Polres Cirebon Kota - Darlian, Fitra (Indonesian Journal of Police Studies, 2020)
This research is motivated by the continued emergence of criminal acts of fraud in the Cirebon City Police Legal Area, even cases of fraud with large material losses. Repressive efforts to fraud cases do not solve the problem because the material losses caused by it will not return to the victim. Thus, the most effective effort is preventive effort. Therefore, a study was conducted which aimed to find out the description of counseling carried out by Satbinmas, the steps to implement binluh, and the influencing factors. This research was conducted with a qualitative approach, using descriptive analysis research methods, as well as data collection techniques through interviews, observations, and document review. Data analysis techniques with data reduction, data presentation, and drawing conclusions. The results found that the Satbinmas counseling counseling activities analyzed by Articles 8, 9, 10, and 11 Perkap Number 21 of 2007 were stillnot optimal. Analysis of the results of the implementation of counseling guidance activities with Articles 19, 20, 21, and 22 Perkap Number 3 of 2015 shows the activity is not optimal by only fulfilling two assessment indicators namely the intensity aspects of officers and community communication forum activities and the intensity in FKPM. Based on the results of the study, the authors suggest adjusting job description and HTCK Satbinmas, adjusting rank and number of Satbinmas personnel, writing SOPs binluh, submitting binluh material with actual issues equipped with clarification, procurement of official inventory items to support counseling and transportation, optimizing analysis and evaluation by Kasat Binmas, providing training / dikjur about counseling, equipping officers with the ability to master the audience and communication science.